Influence of Cash Playback and Receivable Round Towards Return on Assets - Hasanudin Hasanudin (JASa (Jurnal Akuntansi, Audit dan Sistem Informasi Akuntansi), 2020)
This study aims to determine the Effect of Cash Turnover and Accounts Receivable Turnover on Return on Assets at PT. Fubrika Lestari in Jakarta. The method used was explanatory research with a sample of 85 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this study Cash Turnover has no significant effect on Return on Assets of 5.0%, the hypothesis test obtained significance of 0.593> 0.05. Accounts Receivable Turnover did not significantly influence the Return on Assets of 62.9%, the hypothesis test obtained a significance of 0.019 <0.05. Cash Turnover and Receivable Turnover simultaneously have a significant effect on Return on Assets of 85.5%, the hypothesis test obtained significance of 0.008 <0.05.